Probabilistic Model of Surface Crack on the Lumbar Vertebra - Zulkifli, Ahmad@Manap; Ahmad Kamal, Ariffin; Mohd Akramin, Mohd Romlay (Trans Tech Publications, Switzerland, 2014)
The objectives of this study are to determine the stress intensity factor (SIF) for different surface crack size of the lumbar vertebra and the probability of failure associated with finite element method. In this work, all the model components were meshed using the tetrahedral solid element. In order to simplify the model, all the spinal components were modeled as an isotropic and elastic material. Monte Carlo Simulation (MCS) technique was performed to conduct the probabilistic analysis using a probabilistic module in ANSYS with attempt for 100 trials. The results are observed that the maximum SIF were found in the end of crack path with 0.53 MPa.m1/2 and the corresponding probability of failure for the model is 1.22%. Sensitivity analysis had been revealed that the crack size was sensitive to the maximum stress and maximum SIF output parameters with correlation 0.989 and 0.811 respectively. The current probabilistic study is useful as a tool to understand the inherent uncertainties and variations in biological models.